Fuzzy Logic Approach for Person Authentication Based on Palmprint - Mehar, Rajkumar; Kumar Nagwanshi, Kapil (Transactions on Engineering and Computing Sciences, 2014)
The aim of present research is to classify the palmprint images using fuzzy logic for different security aspects. Fuzzy logic is relatively efficient and advanced theory, at present wide use of fuzzy logic is in the classification of remotely sensed images. A branch of biometric, palmprint authentication have increasing attention because palmprint is unique, permanent, measurable characteristics having voluminous of the line features. In this paper we discuss a method for feature extraction, identification (recognition) techniques of palmprints based on fuzzy logic technique and some publically available databases. This method use sub image based principle line feature extraction technique in low resolution palmprint images. Image is divided into sub images and feature obtained from these subimages are combined to generate a single feature vector for the palmprint image. This vector is provides to fuzzy inference system as input. The testing for system has been performed on IITD, and PolyU databases. Experiments were carried to show the effectualness of our proposed approach have an accuracy of 89.46%.